Genetic Analysis of F4 Rice Lines for Salt Tolerance at the Reproductive Stage (Progressive Agriculture, 2013)
A total of 29 lines of F4 population of rice along with their parents Binadhan-5 (high yielding and salt susceptible) and Harkuch (salt tolerant landrace) were evaluated for salt tolerance at the reproductive stage with EC 6 dS/m following IRRI standard protocol. High heritability coupled with high genetic advance was observed in plant height in salinized and non-salinized conditions. High heritability along with high genetic advance was also found in number of filled grains/plant in saline condition. These characters were under additive gene control and selection for salt tolerance might be effective. Number of filled grains/plant showed significant positive correlation with grain yield/plant. Path analysis revealed that number of filled grains/plant had positive and maximum direct effect on grain yield/plant. Therefore, number of filled grains/plant should be given the importance in selection of rice lines under saline condition.DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16746 Progress. Agric. 21(1 & 2): 31 - 38, 2010